Deploying two-stage anaerobic process to co-digest greasy sludge and waste activated sludge for effective waste treatment and biogas recovery. (15th August 2022) - Sani, Khaliyah; Jariyaboon, Rattana; O-Thong, Sompong; Cheirsilp, Benjamas; Kaparaju, Prasad; Raketh, Marisa; Kongjan, Prawit
Abstract: High-strength waste activated sludge (WAS) and greasy sludge (GS) were largely generated from canned tuna processing. This study reports the performance of the two-stage anaerobic process for co-digesting WAS and GS. Various WAS:GS mixing ratios of 0:100, 10:90, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 80:20, 90:10, and 100:00 (volatile solids (VS) basis) were investigated in batch acidogenic stage at ambient (30 °C ± 3 °C), 55 °C, and 60 °C temperatures. Subsequently, the effluents from the first stage were used to produce methane in the second methanogenic stage at an ambient temperature. The highest methane yield of 609 mL CH4 /g-VSadded was achieved using acidogenic effluents generated from a WAS:GS mixing ratio of 40:60 at an ambient temperature. The first-order kinetic constants (k) for the first (k1 ) and second (k2 ) stages were subsequently estimated to be 0.457 d −1 and 0.139 d −1, respectively. The obtained k constants were further used to predict the hydraulic retention time (HRT) for the two continuously stirred tank reactors (CSTR) in series. Consequently, the calculated 4-day HRT and 20-day HRT for 50-L CSTR1 and 250-L CSTR2, respectively, were used to operate the continuous two-stage process at an ambient temperature by feeding with a 40:60-WAS:GS mixing ratio. A satisfactory methane yield of 470-mL CH4 /g-VS along with 75% chemical oxygen demand (COD) removal was generated. Furthermore, the predicted methane yield of 450-mL CH4 /g-VS obtained from the simple kinetic CSTR model resembled the experimental yield with 96% accuracy. The obtained experimental results demonstrate that WAS and GS co-digestion could be successfully accomplished using a practical two-stage anaerobic process operated at an ambient temperature. Highlights: The waste-activated sludge portion of 40% (g-VS) provides the highest methane yield. The highest synergistic effect of this co-digestion was obtained at C/N ratio of 30. The highest methane yield obtained from first stage effluent at ambient temperature. A first-order kinetic constant works well for methane prediction with 96% accuracy. Methane yield of 470 mL-CH4 /g-VS, with 75 %COD removal was obtained from two CSTRs.